Evaluation and Strengthening of Risk Culture at PT Bank ABC in Digital Transformation - Mohamad Hendra Budiawan; Zaenal Abidin (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to evaluate the risk culture at PT Bank ABC using the Sound Risk Culture Indicators framework from the Financial Stability Board (FSB). A strong risk culture is a crucial element in banking risk management, particularly in ensuring business sustainability and regulatory compliance. This study is conducted in the context of Bank ABC’s transformation from a traditional bank into a digital bank following its acquisition by PT JKL Group and PT DEF. This research adopts a qualitative case study approach, collecting data through questionnaires, semi-structured interviews, and a review of internal company documents. The respondents include executive officers, the head of the risk management division, the head of the human resources division, and employees involved in risk management. The findings indicate that Bank ABC has a relatively strong risk culture, particularly in the aspects of tone from the top, accountability, and risk communication. However, several challenges remain, such as the lack of a comprehensive assessment of risk culture maturity and limitations in escalation mechanisms and risk-based incentives. Operational risks, particularly those related to internal fraud and process errors, remain a key concern. By implementing the recommendations based on the FSB Sound Risk Culture Indicators, Bank ABC is expected to further enhance the effectiveness of its risk management, supporting its digital transformation and improving overall risk governance.